ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN UPAH MINIMUM TERHADAP PENYERAPAN TENAGA KERJA DI PROVINSI MALUKU TAHUN 2015-2024 - Sahrul, Sahrul; Zainudin, The Ode (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2025)
Population growth in Maluku Province is increasing day by day. Population growth will certainly result in an increase in the number of workers, but an increase in the number of workers will become a problem in the world of employment if the number of available workers is not proportional to the amount of labor demand. This problem is important because it is closely related to unemployment which will increase the possibility of poverty and socio-economic phenomena in society. This study aims to determine the effect of economic growth as measured by GRDP at constant prices and provincial minimum wage on labor absorption in Maluku Province. The data used is time series data from 2015-2024. The data analysis model uses Multiple Linear Regression with the help of Eviews 12 software. It is known that the partial results of the study, namely economic growth as measured by GRDP, has a positive and significant effect on employment in Maluku Province, while the provincial minimum wage has a positive but insignificant effect on employment in Maluku Province. And simultaneously GRDP and minimum wage together have a significant influence on employment in Maluku Province. Keyword: GRDP, Minimum Wage and Labour